Droplet deposition and efficiency of fungicides sprayed with small UAV against wheat powdery mildew - Qin, Weicai; Xue, Xinyu; Zhang, Shaoming; Gu, Wei; Wang, Baokun (International Journal of Agricultural and Biological Engineering, 2018)
Small unmanned aerial vehicle (UAV), a timely and effective pesticide sprayer, can be used to spray pesticide in a high efficiency without harming the crop, and is especially suitable for spraying for small farms and hills in Asian countries. In recent years, it has been chosen as a key and new technique for pesticide application. This paper studied the impact of UAV (UAV N-3) spraying parameters (different working height and different spraying concentrations) on the deposition of droplets on the wheat canopy and the prevention of powdery mildew. Water sensitive paper was used as the sampler to collect the pesticide droplets and image processing software Deposit Scan was used to compute the coverage rate of droplets on the wheat top layer to acquire the proportional distribution of droplets on the wheat lower layer. The experimental results showed the impact of spraying height on the distribution of droplets on the wheat upper layer was quite significant, when the spraying height was 5.0 m and the spraying speed was 4 m/s, the coverage rate of droplets on the wheat lower layer was the largest, as it was 45.6% of that on the upper layer, the droplets distribution was the most uniform, and the coefficient of variation was 33.13%. 450 g/hm2 (dosage registered) of triadimefon SC (44%) was sprayed by the UAV, the control efficiency reached 55.1% after applying which was better than 20% and 40% of dosage decreased for each hectare, and the applying effect (35.6%) of 20% dosage decreased for each hectare had no significant difference from the applying effect (34.6%) applied by a knapsack-type electric sprayer. At 10 d after applying, the prevention effect realized by UAV was lower than that realized by a knapsack-type electric sprayer, and it may be correlated to the meteorological condition and water amount in the pesticide sprayed. Thus, when UAV spraying was chosen to prevent wheat powdery mildew under a serious disease situation, an auxiliary agent for spraying could be added to prolong the retention of pesticide on the plant surface to extend the pesticide effect. This study can provide a reference for the optimized design, performance upgrade and reasonable application of small UAV sprayers.Keywords: unmanned aerial vehicle (UAV), spraying pesticide, parameters optimization, fungicide deposition, wheat powdery mildew, control effectDOI: 10.25165/j.ijabe.20181102.3157Citation: Qin W C, Xue X Y, Zhang S M, Gu W, Wang B K. Droplet deposition and efficiency of fungicides sprayed with small UAV against wheat powdery mildew. Int J Agric & Biol Eng, 2018; 11(2): 27–32.